MicroRNA-186-5p mediates osteoblastic differentiation and cell viability by targeting CXCL13 in non-traumatic osteonecrosis - Xu, Weihua (Mol Med Rep, 2019)
MicroRNAs (miRs) serve varying and important roles in the pathogenesis of non-traumatic osteonecrosis (ON). However, the role miR-186-5p serves in the pathogenesis of osteonecrosis remains unknown and the clinical outcome of ON is still uncertain. The aim of the present study was to determine the expression characteristics, biological function and molecular mechanisms of miR-186-5p, which is associated with cancer development and progression, in osteoblastic differentiation and cell viability. The results of the present study showed that the expression levels of miR-186-5p were significantly higher in clinical non-traumatic ON compared with osteoarthritis samples (P=0.0001). An inverse association was observed between miR-186-5p and CXCL13 expression levels. Furthermore, miR-186-5p inhibited phosphatidylinositol 3 kinase (PI3K)/protein kinase B (AKT) signaling, downregulated osteoblast-specific markers and reduced the viability and differentiation of human mesenchymal stem cells from bone marrow (HMSC-bm) through targeting CXCL13. Increasing expression of CXCL13 in HMSC-bm cells partially restored miR-186-5p-mediated inhibition. In conclusion, abrogation of PI3K/AKT signaling triggered by miR-186-5p/CXCL13 may contribute to ON pathogenesis. These results highlight the possible clinical value of miR-186-5p in treatment for non-traumatic ON.